2014
DOI: 10.7202/1024903ar
|View full text |Cite
|
Sign up to set email alerts
|

Les résidences pour personnes âgées de l’île de Montréal appartenant aux parcs social et privé : une exposition inéquitable à la pollution de l’air ?

Abstract: Résumé La qualité des milieux à proximité des résidences pour personnes âgées sur l’île de Montréal, tant celles du parc privé que du parc social, est analysée sous l’angle de la pollution générée par la circulation automobile. Deux types d’indicateurs de polluants sont utilisés pour évaluer la pollution. Les premiers sont basés sur la proximité des axes majeurs de circulation et les seconds estiment, dans un rayon de 200 m, la concentration de NO2. Nos résultats montrent que les résidences privées e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These spaces are above all characterized by higher residential density, the diversity of urban functions, and the greater concentration and lengths of collector roads, arteries, expressways, and highways that link together the main poles of attraction on the Island of Montreal, as well as the access toward the bridges and the major suburbs of the CMA, hence the higher traffic data volumes. So the geography of road transportation and the location of this group in the centre of the Island of Montreal explain, in part at least, the higher concentration of pollutants for this group (Carrier et al, 2014). The values of some of the pollution indicators are thus more strongly explained by the presence of individuals from lowincome households.…”
Section: Discussionmentioning
confidence: 92%
“…These spaces are above all characterized by higher residential density, the diversity of urban functions, and the greater concentration and lengths of collector roads, arteries, expressways, and highways that link together the main poles of attraction on the Island of Montreal, as well as the access toward the bridges and the major suburbs of the CMA, hence the higher traffic data volumes. So the geography of road transportation and the location of this group in the centre of the Island of Montreal explain, in part at least, the higher concentration of pollutants for this group (Carrier et al, 2014). The values of some of the pollution indicators are thus more strongly explained by the presence of individuals from lowincome households.…”
Section: Discussionmentioning
confidence: 92%
“…These results are surprising given that few studies in environmental equity have considered this population group. This situation can be explained by the overrepresentation of this group outside Montréal’s central neighbourhoods ( Séguin et al, 2013 ), in sectors characterized by a strong presence of private seniors residences ( Carrier et al, 2013 ). Considering these results, this group should be more often included in the work on environmental equity related to aircraft noise.…”
Section: Discussionmentioning
confidence: 99%
“…The portions that we have excluded from the study area represent approximately 400,000 people: that is, 24% of the Island's population). The study area, shown in Figure 2, does however include all the sections of highway and the main arterial and collector roads that connect the City of Montreal to its suburbs (Carrier et al, 2013). The central Island of Montreal boroughs also represent a major employment pole for the 3.92 million inhabitants of the Montreal Metropolitan Community (MMC) (Carrier et al, 2016).…”
Section: Study Areamentioning
confidence: 99%